The Use of Idol Media to Improve Students' Biographical Text Writing Skills - Wardoyo, Hadi; Akbar, Akbar; Wulandari, Jekti (Educare : Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
One of the important factors in the success of learning is the selection of media that is in accordance with the teaching material. Based on the results of observations in class X-5 of SMA Negeri 6 Malang, it was found that the ability to write student biographical texts is still low. Students have difficulty in developing ideas systematically and using the right language according to the biographical structure. To overcome these problems, this study applies the media of idol figures in learning to write biographical texts. This study is a Kemmis and McTaggart model class action research which was carried out in two cycles and involved 36 students in class X-5 as research subjects. Data were collected through a biographical writing test conducted before and after the action, then analyzed quantitatively using SPSS 27 to calculate the average score. The results showed that the average score of students before the action was 72.69. After the implementation of idol figure media, the average score increased to 78.47 in the first cycle and 85.61 in the second cycle. These results prove that the use of idol media is effective in improving students' biographical text writing skills. The implication is that the media of idol figures can be recommended as an alternative learning strategy to improve students' writing skills in secondary school.